Low plasma levels of BTLA and LAG-3 before HCV therapy are associated with metabolic disorders after HCV eradication in persons with HIV/HCV coinfection: a retrospective study - Martín-Escolano, Rubén; Virseda-Berdices, Ana; Berenguer, Juan; González-García, Juan; Brochado-Kith, Oscar; Fernández-Rodríguez, Amanda; Díez, Cristina; Hontañon, Victor; , The Marathon Study Group; Resino, Salvador; Jiménez-Sousa, María Ángeles; Arranz, A.; et al. (Frontiers in Pharmacology, 2024)
Background: Understanding the predictors of metabolic disorders in persons with HIV/HCV coinfection post-HCV therapy is crucial for improving patient outcomes. Since immune checkpoint proteins are usually upregulated in these persons with HIV/HCV coinfection, we aimed to evaluate the association between plasma immune checkpoint proteins at baseline (before HCV therapy) and metabolic disturbances during the follow-up (about five years after successful HCV treatment) in persons with HIV/HCV coinfection.We performed a retrospective study on 80 persons with HIV/HCV coinfection with advanced fibrosis or cirrhosis who cleared HCV infection after successful HCV therapy and were followed for about 5 years after completion of HCV treatment. Plasma samples were collected at baseline. Immune checkpoint proteins were analyzed using a Luminex 200 TM analyzer. Outcomes were the development of a metabolic event (type 2 diabetes mellitus and/or dyslipidemia) and the change in Triglycerides and glucose (TyG) index.Results: During follow-up, 21 (26%) patients developed metabolic events (type 2 diabetes mellitus/ dyslipidemia), and 29 (46.0%) patients had an increase in TyG during the follow-up.Low baseline values of BTLA and LAG-3, two immune checkpoint proteins, were associated with the development of metabolic events (aAMR= 0.69 and aAMR= 0.71, respectively) and with increases in TyG values (aAMR= 0.72 and aAMR= 0.70, respectively). In addition, other immune checkpoint proteins were also inversely associated with increases in TyG.We discovered that low plasma levels of BTLA and LAG-3 before HCV therapy significantly correlate with an increased risk of developing metabolic disorders after treatment.